Segmentasi Citra Tulang Belakang Menggunakan Charged Particle Model - Mujahidin, Alif Aziz; Rasmana, Susijanto Tri; Wibowo, Madha Christian; Wirakusuma, Sandy (Journal of Control and Network Systems, 2014)
Scoliosis is a spinal abnormalities that bends to S shape or C shape. The proper treatment can make better healing of scoliosis patient. Currently, diagnosis of spinal curvature is using a manual process performed by orthopedic, thus resulting an error in the measurement. To resolve this issue, used segmentation method that using image processing technology. segmentation method is using Charged Particle Model (CPM) which able to perform segmentation properly.